Selective electron beam melting of Al0.5CrMoNbTa0.5 high entropy alloys using elemental powder blend. Issue 2 (February 2019) - Popov, Vladimir V.; Katz-Demyanetz, Alexander; Koptyug, Andrey; Bamberger, Menachem
Abstract: High Entropy Alloys (HEAs) is a novel promising class of multi-component materials which may demonstrate superior mechanical properties useful for high-temperature applications. Despite the high potential of HEAs, their production is complicated, using pre-alloyed powders in powder metallurgy route. This significantly complicates development and implementation of refractory BCC solid solution based HEAs. The present paper reports on experiments aiming at production of Al0.5CrMoNbTa0.5 multi-principle alloy using powder bed beam based additive manufacturing. Samples were manufactured using Selective Electron Beam Melting (SEBM) additive manufacturing technique from a blend of elemental powders aiming at achieving microstructure with high configurational entropy. Though it was not possible to achieve completely homogeneous microstructure, the as-printed material was composed of the zones with two multi-component solid solutions, which differed only by Al content confirming in situ alloying. The process parameters optimization was not carried out and the as-print material contained a notable amount of residual porosity. It was possible to reach lower porosity level using heat treatment at 1300 °C for 24 hours, however undesirable alloy composition changes took place. The main conclusion is that the production of the Al0.5CrMoNbTa0.5 multi-principle alloy from elemental powder blends using SEBM technique is achievable, but the process parameter optimization rather than post-process heat treatment should be performed to reduce the porosity of samples.